Application of the life experiences program to the evaluation of teachers of IE N° 5168 Rosa Luz of the Puente Piedra district, 2018 - Chipana Tucno, Lucila (2022)
The study conducted is an applied experiment whose goal was to ascertain the impact of using the program's experiential experiences in evaluating instructors at I.E. N ° 5168 Rosa Luz in the Puente Piedra district in 2018. This study takes an experimental approach. This study's depth or breadth provides context for its findings. The instrument underwent a process of validity and reliability before being applied, and a structured questionnaire was prepared for the evaluation of teachers; the population was made up of 40 teachers from I.E. N ° 5168 Rosa Luz of the Puente Piedra district; the sample was split into two groups, each of which included 20 educators; and the two groups were compared to one another. The program's five sessions were built through the instructors' collaboration over the course of two hours; each session began with a pre-session assessment, moved through the program's content, and concluded with a post-session evaluation. Having established that in the postest the value of p = 0.000 0.05, the findings show that the implementation of the program experiential experiences effects the assessment of instructors at I.E. N ° 5168 Rosa Luz in the Puente Piedra district.